Educare alle differenze nella scuola primaria: tra pratiche e ruoli - Santoni, Claudia (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
This paper relates two areas of gender’s action used as a cognitive-interpratative category. On the one hand it deals with gender education – better known as education to differences – as a training approach aimed at containing disparities, stereotypes and violence, on the other, gender belonging of teachers school, particulary those who teach in the primary school, that is almost totally feminized, such as determinant of the professional identity.